Dysregulation of regulatory CD56bright NK cells/T cells interactions in multiple sclerosis. (August 2016) - Laroni, Alice; Armentani, Eric; Kerlero de Rosbo, Nicole; Ivaldi, Federico; Marcenaro, Emanuela; Sivori, Simona; Gandhi, Roopali; Weiner, Howard L.; Moretta, Alessandro; Mancardi, Giovanni L.; Uccelli, Antonio
Abstract: Recent evidence has shown that CD56 bright NK cells, a subset of NK cells abundant in lymph nodes, may have an immunoregulatory function. In multiple sclerosis (MS), expansion of CD56 bright NK cells has been associated to successful response to different treatments and to remission of disease during pregnancy; how whether they exert immunoregulation in physiologic conditions and whether this is impaired in MS is not known. We dissected the immunoregulatory role of CD56 bright NK cells function in healthy subjects (HS) and compared it with that of untreated MS subjects or patients with clinically isolated syndrome suggestive of MS (CIS). We found that CD56 bright NK cells from HS acquire, upon inflammatory cues, the capability of suppressing autologous CD4+T cell proliferation through direct cytotoxicity requiring engagement of natural cytotoxicity receptors (NCRs) and secretion of granzyme B. CD56 bright NK cells from patients with MS/CIS did not differ in frequency and share a similar phenotype but displayed a significantly lower ability to inhibit autologous T cell proliferation. This impairment was not related to deficient expression of NCRs or granzyme B by CD56 bright NK cells, but to increased HLA-E expression on T cells from MS/CIS subjects, which could enhance the inhibitory effect mediated by NKG2A that is homogeneously expressed on CD56 bright NK cells. The defect in controlling autologous T cells by CD56 bright NK cells in MS/CIS might contribute to the excess of autoimmune response that is associated to disease development. Graphical abstract: Highlights: CD56 bright NK cells suppress autologous T-cell proliferation through cytotoxicity in health. Cytotoxicity of CD56 bright NK cells requires engagement of the NCRs. Cytotoxicity of CD56 bright NK cells involves release of granzyme B. Suppressor function of CD56 bright NK cells is impaired in multiple sclerosis. Increased HLA-E expression on MS T cells blocks suppression by CD56 bright NK cells.